Anti-biofilm and Antibacterial Activities of Silver Nanoparticles Synthesized by the Reducing Activity of Phytoconstituents Present in the Indian Medicinal Plants - Mohanta, Yugal Kishore; Biswas, Kunal; Jena, Santosh Kumar; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Mohanta, Tapan Kumar (Frontiers in Microbiology, 2020)
Biofilm formation by a variety of microbial pathogens can be a serious health hazard that is difficult to combat. Nanotechnology, however, represents a new approach to fighting and eradicating biofilm forming microorganisms. In the present study, the sustainable synthesis and characterization of biocompatible silver nanoparticles (AgNPs) from leaf extracts of Semecarpus anacardium, Glochidion lanceolarium, and Bridelia retusa was explored. Continuous synthesis was observed in a UV-vis spectroscopic analysis and the participating phytoconstituents, flavonoids, phenolic compounds, phytosterols, and glycosides, were characterized by ATR-FTIR spectroscopy. The size and surface charge of the particles were also measured by dynamic light scattering spectroscopy. Scanning electron microscopy study was employed to examine the morphology of the nanoparticles. The spectroscopic and microscopic study confirmed the successful synthesis of AgNPs by plant extracts acting as strong reducing agents. The synthesized AgNPs were screened for antibacterial and anti-biofilm activity against human pathogens Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus. Results of the study demonstrate the potential of phyto-synthesized AgNPs as potential anti-biofilm agents and for other biomedical applications.